Synthetic Lethality of a Novel Small Molecule Against Mutant KRAS-Expressing Cancer Cells Involves AKT-Dependent ROS Production - Iskandar, K.; Rezlan, M.; Yadav, S.; Foo, C.; Sethi, G.; Qiang, Y.; Bellot, G.; Pervaiz, Shazib (Mary Ann Liebert, Inc. Publishers, 2016)
© 2016 Mary Ann Liebert, Inc. We recently reported the death-inducing activity of a small-molecule compound, C1, which triggered reactive oxygen species (ROS)-dependent autophagy-associated apoptosis in a variety of human cancer cell lines. In this study, we examine the ability of the compound to specifically target cancer cells harboring mutant KRAS with minimal activity against wild-type (WT) RAS-expressing cells. Results: HCT116 cells expressing mutated KRAS are susceptible, while the WT-expressing HT29 cells are resistant. Interestingly, C1 triggers activation of mutant RAS, which results in the downstream phosphorylation and activation of AKT/PKB. Gene knockdown of KRAS or AKT or their pharmacological inhibition resulted in the abrogation of C1-induced ROS production and rescued tumor colony-forming ability. We also made use of HCT116 mutant KRAS knockout (KO) cells, which express only a single WT KRAS allele. Exposure of KO cells to C1 failed to increase mitochondrial ROS and cell death, unlike the parental cells harboring mutant KRAS. Similarly, mutant KRAS-transformed prostate epithelial cells (RWPE-1-RAS) were more sensitive to the ROS-producing and death-inducing effects of C1 than the vector only expressing RWPE-1 cells. An in vivo model of xenograft tumors generated with HCT116 KRASWT/MUT or KRASWT/- cells showed the efficacy of C1 treatment and its ability to affect the relative mitotic index in tumors harboring KRAS mutant. Innovation and Conclusion: These data indicate a synthetic lethal effect against cells carrying mutant KRAS, which could have therapeutic implications given the paucity of KRAS-specific chemotherapeutic strategies.